Profitability Dynamics of Sharia Financing Companies in Indonesia: Forward and Backward Method Perspectives (2017–2022) - Zikriatul Ulya (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2025)
Sharia-compliant financing companies in Indonesia experienced fluctuations in net profit during the 2017–2022 period, influenced by developments in murabahah financing, investment financing, and service financing. This dynamic suggests the need for in-depth analysis to identify the factors most influential on net profit. This study employed a quantitative approach with secondary data in the form of 72 monthly reports from Sharia-compliant financing companies in Indonesia for the 2017–2022 period. Data collection was conducted through documentation, while the analysis method used was multiple linear regression using forward and backward regression, accompanied by classical assumption testing and hypothesis testing. The results indicate that murabahah financing has a negative and insignificant effect on net profit. Conversely, investment financing has a positive and significant effect, while service financing has a negative and insignificant effect on net profit. However, simultaneously, all three variables have a positive and significant effect on net profit of Sharia-compliant financing companies in Indonesia.